1967
DOI: 10.1139/b67-041
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Crown Rot of Boxed Bananas in Relation to Microbial Populations of the Crown Tissue

Abstract: During a period of 10 months, weekly samples were taken of rotted banana crowns to determine the microorganisms associated with rot. On a total of 648 crowns, Cephalosporium sp. occurred on 93%, Verticillium theobromae 81%, Fusarium roseum 'Gibbosum' 80%, F. moniliforme 14%, Botryodiplodia theobromae 12%, and Gloeosporium musarum 3%. Isolates of these organisms from green crowns, bracts, flowers, and petioles of the banana plant were able to rot crown segments in laboratory tests. Cephalosporium sp. has been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 1 publication
0
28
0
Order By: Relevance
“…Seasonal fluctuations in crown rot severity have already been reported for situations of natural contamination (Griffee, 1971;Lukezic et al, 1967;Shillingford, 1978), but the present investigation is the first report of such fluctuations in the case of artificial contaminations.…”
Section: Variation Of the Susceptibility Of Bananas To Crown Rot Disementioning
confidence: 45%
See 2 more Smart Citations
“…Seasonal fluctuations in crown rot severity have already been reported for situations of natural contamination (Griffee, 1971;Lukezic et al, 1967;Shillingford, 1978), but the present investigation is the first report of such fluctuations in the case of artificial contaminations.…”
Section: Variation Of the Susceptibility Of Bananas To Crown Rot Disementioning
confidence: 45%
“…Finlay and Brown (1993) have found C. musae to be 20 times more pathogenic than Fusarium spp. Other authors have highlighted that C. musae can initiate infection from a low inoculum concentration (Finlay and Brown, 1993;Greene and Goos, 1963;Lukezic et al, 1967;Shillingford, 1976) and that other pathogens require much higher inoculum concentration to induce symptoms (Finlay and Brown, 1993;Griffee, 1971;Krauss, 1996;Krauss et al, 1998). Interestingly, the rotting effect induced by C. musae in our untreated control was greater when the pathogen was inoculated alone than in mixture with other fungi at the same final concentration.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…It is caused by a large complex of fungal pathogens varying according to the geographic location and time of year (Meredith, 1971). Among the organisms composing this complex, Colletotrichum musae is often regarded as the most pathogenic (Greene and Goos, 1963;Lukezic et al, 1967;Shillingford, 1976;Finlay and Brown, 1993;Lassois et al, 2008). First symptoms may be observed after shipment, increasing rapidly during fruit ripening (Slabaugh and Grove, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Variations, notably geographic and seasonal, have been reported in the postharvest development of crown rot disease symptoms (Krauss and Johanson 2000;Lassois et al 2008;Lukezic et al 1967;Shillingford 1978). It has been suggested that these spatiotemporal fluctuations reflect the variations in the banana fruit quality potential that elaborates during preharvest stages (Lassois et al 2010b).…”
mentioning
confidence: 99%